2016
DOI: 10.1097/mao.0000000000001163
|View full text |Cite
|
Sign up to set email alerts
|

Music-induced Hearing Loss in Children, Adolescents, and Young Adults

Abstract: The prevalence of increased hearing levels (>15 dB HL) was 9.6%, and high-frequency hearing loss was found in 9.3%. The average hearing thresholds were 4.79 dB HL at low frequencies (0.5, 1, and 2 kHz) and 9.54 dB HL at high frequencies (3, 4, and 6 kHz). Most studies reported no significant association between pure-tone air thresholds and exposure to loud music. However, significant changes in hearing thresholds and otoacoustic emissions, and a high tinnitus prevalence suggest an association between music exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 38 publications
2
39
0
2
Order By: Relevance
“…In addition, several studies have demonstrated that maximum outputs of PLDs can exceed 125 dBA [8]. The preferred listening levels (PLLs) adopted by young users range from 71 to 105 dBA [5,9,10], but approximately 58% of adolescents and college students have exceeded that recommended maximum noise exposure [11], and the prevalence of increased hearing thresholds due to public music exposure via PLDs has not been overlooked [12]. Furthermore, various studies have reported an association between exposure to music at a high intensity and hearing deterioration, including temporary threshold shifts (TTS), tinnitus, hyperacusis, and recruitment, all of which eventually produce permanent hearing loss to the users [2,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have demonstrated that maximum outputs of PLDs can exceed 125 dBA [8]. The preferred listening levels (PLLs) adopted by young users range from 71 to 105 dBA [5,9,10], but approximately 58% of adolescents and college students have exceeded that recommended maximum noise exposure [11], and the prevalence of increased hearing thresholds due to public music exposure via PLDs has not been overlooked [12]. Furthermore, various studies have reported an association between exposure to music at a high intensity and hearing deterioration, including temporary threshold shifts (TTS), tinnitus, hyperacusis, and recruitment, all of which eventually produce permanent hearing loss to the users [2,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various studies have reported an association between exposure to music at a high intensity and hearing deterioration, including temporary threshold shifts (TTS), tinnitus, hyperacusis, and recruitment, all of which eventually produce permanent hearing loss to the users [2,13,14]. In other words, such hearing deterioration seems to be temporary and quickly recovered at an early stage of music exposure; however, these temporary changes can naturally develop into a permanent hearing loss from habituated and accumulated exposure [12] and then accelerate into an age-related hearing loss [15].…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al (2016) found that a large proportion of adolescents and young adults that use personal music players are at risk of noise-induced hearing loss, especially when they listen to music at volumes exceeding 65 dB for extended periods of time. In a recently published systematic review, hearing thresholds at higher frequencies (4-16 kHz) were significantly poorer in personal music player users when compared with control subjects (le Clercq et al 2016). In this way, noise-induced hearing loss is no longer limited to occupational exposure to sustained noise, but is becoming increasingly common in recreational settings.…”
Section: Hearing Loss and Hearing-related Disordersmentioning
confidence: 96%
“…However, depending on time of use, volume and type of device, music listening behaviors may harm people's health. Therefore, several studies have begun to seek and report the risks posed by this habit (1,2) .…”
Section: Introductionmentioning
confidence: 99%